A novel genetic strategy to interrogate an unknown phenotypic modifier: Sdhc KO-Robertsonian mice develop frequent thyroid abnormalities with papillary thyroid carcinoma-like features - Jean-Pierre Bayley; Heggert G. Rebel; Peter Devilee (PLoS ONE, 2026)
Genes encoding subunits of the mitochondrial tricarboxylic acid cycle enzyme complex succinate dehydrogenase (SDH) are a leading cause of the neuroendocrine tumour syndrome hereditary paraganglioma-pheochromocytoma. Pathogenic variants of SDHD and SDHAF2 confer a remarkable parent-of-origin tumour risk, in which paternally inherited variants cause tumours but maternally inherited variants do not. Formulated to explain this observation, the Hensen hypothesis proposes that loss of an (unknown) imprinted gene(s), together with the remaining wildtype SDH gene, is a prerequisite for tumour formation; in effect a three-hit hypothesis. This study had three objectives, first, as a test of the Hensen model, second, as a potential model for a disease for which no mouse or cell model currently exists, and finally, as a test of chromosome (Ch.) configuration to interrogate large genomic regions carrying an unknown phenotypic modifier. We crossed a gene knockout line ( Sdhc, mouse Ch.1) to a Robertsonian chromosome line, Rb(1:7), harbouring the homologous gene imprinting centre (human Ch.11p15, mouse Ch.7) implicated in human tumourigenesis, to create a metacentric chromosome with characteristics of human chromosome 11. We developed 7 cohorts combining Sdhc (mouse Ch.1) wildtype or knockout with distinct configurations of Rb(1:7), confirming both paternal and maternal inheritance of Sdhc . We noted significant weight gain, and in heterozygote Sdhc KO-Rb/wt mice high levels of immune activation. Thyroid abnormalities, including lesions with papillary thyroid carcinoma-like features, were common (30–50%) in Sdhc knockout mice with both heterozygous and homozygous Rb chromosomes, regardless of mode of inheritance. We also observed a single case of bilateral pheochromocytoma in which loss of Sdhc was not the driver. While our findings did not recapitulate features of the Hensen Model, this study does suggest that chromosomal structure, even in the form of a seemingly innocuous single Robertsonian configuration, can dramatically impact clinical phenotype.